(untitled) (Research, Society and Development, 2022)
Objective: toevaluatethefrequencyandfactorsassociatedwiththeconcentrationof abdominal fat in health workers at a public university. Methods: cross-sectional study carried out with health workers at UFPE, in the city of Recife/PE/Brazil. Demographic (sex and age), socioeconomic (educational level) and lifestyle (physical activity, smoking and drinking) data were collected; anthropometry for the diagnosis of global/abdominal obesity, performed by body mass index (BMI) and waist circumference (WC), respectively. Results: there was a predominance of overweight (60.0%), with 20.0% obese, with no statistical difference between the sexes. Abdominal obesity was detected in 56.3% of men and 81.6% of women, with a statistically significant association between abdominal obesity and female sex, age  50 years and BMI in the overweight range. Conclusion: abdominal obesity was high in this group, with a higher prevalence in women. This frequency follows the Brazilian and global trend of this condition.